CURRENT TRENDS IN THE APPLICATION OF AUGMENTED REALITY-BASED LEARNING MEDIA IN BIOLOGY EDUCATION: A SYSTEMATIC LITERATURE REVIEW - Ramadhini, Ineke Laili; Marlina, Reni; Titin, Titin (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
The development of digital technology has brought significant changes to the world of education, including in Biology learning, which often contains abstract concepts that are difficult to visualize. One innovation that is widely used to overcome this problem is Augmented Reality (AR) technology. AR allows students to interact with three-dimensional virtual objects in a realistic way, thereby improving their understanding of complex Biology concepts. This study aims to analyze the latest trends in the application of AR-based learning media in biology learning using a Systematic Literature Review (SLR) approach with PRISMA guidelines.  A total of 19 articles published between 2016 and 2025 were reviewed based on inclusion criteria, including formal education levels, types of media, research methods, and biology topics studied. The results of the analysis show that the use of AR is most commonly found at the senior high school level, with smartphone-based media dominating. This is due to the more mature abstract thinking and digital literacy skills of senior high school students, which support the effective use of AR in understanding biology material. Most studies used quantitative methods with quasi-experimental designs to measure the effect of AR on student learning outcomes, motivation, and digital literacy. In general, AR-based media has been proven to improve students' conceptual understanding, learning outcomes, motivation, and engagement in Biology learning. Thus, AR technology has great potential as an innovative 21st-century learning strategy that is interactive, contextual, and supports the digital transformation of Biology education. ABSTRAK Perkembangan teknologi digital telah membawa perubahan signifikan dalam dunia pendidikan, termasuk dalam pembelajaran Biologi yang sering kali memuat konsep abstrak dan sulit divisualisasikan. Salah satu inovasi yang banyak digunakan untuk mengatasi permasalahan tersebut adalah teknologi Augmented Reality (AR). AR memungkinkan siswa berinteraksi dengan objek virtual tiga dimensi secara nyata sehingga dapat meningkatkan pemahaman terhadap konsep Biologi yang kompleks. Penelitian ini bertujuan untuk menganalisis tren terkini penerapan media pembelajaran berbasis AR dalam pembelajaran Biologi menggunakan pendekatan Systematic Literature Review (SLR) dengan panduan PRISMA. Sebanyak 19 artikel yang diterbitkan pada tahun 2016–2025 ditelaah berdasarkan kriteria inklusi, meliputi jenjang pendidikan formal, jenis media, metode penelitian, serta topik Biologi yang dikaji. Hasil analisis menunjukkan bahwa penggunaan AR paling banyak ditemukan pada jenjang Sekolah Menengah Atas (SMA) dengan dominasi media berbasis smartphone. Hal ini dikarenakan kemampuan berpikir abstrak dan literasi digital siswa SMA yang lebih matang, sehingga mendukung efektivitas penggunaan AR dalam memahami materi Biologi. Sebagian besar penelitian menggunakan metode kuantitatif dengan desain quasi-experimental untuk mengukur pengaruh AR terhadap hasil belajar, motivasi, dan literasi digital siswa. Secara umum, media berbasis AR terbukti mampu meningkatkan pemahaman konsep, hasil belajar, motivasi, dan keterlibatan siswa dalam pembelajaran Biologi. Dengan demikian, teknologi AR memiliki potensi besar sebagai strategi pembelajaran inovatif abad ke-21 yang interaktif, kontekstual, dan mendukung transformasi digital pendidikan Biologi.